#TITLE_ALTERNATIVE# - GASIANI (NIM 12007052), DEVI
Osram area is located in North West Java Basin, on the offshore part of the Jatibarang Sub basin. This area is one of considerable potential hydrocarbon basins in Indonesia. In terms of exploration, the area is still being developed to improve oil and gas production. The focus of this research is Member of Main interval which is part of Upper Cibulakan Formation. Up until now, the research interval is one of the exploration targets which are conducted in Jatibarang Sub Basin. This research uses several data, such as well log data and seismic 3D as the main data processing, also, side wall core report, geochemical report, biostratigraphy report, and earlier company data research that will be evaluated. The methods used in this study are well-seismic tie, 3D seismic interpretation, sequence stratigraphy analysis, electrofasies analysis, depositional environment analysis, petrophysics calculation, and Montecarlo Simulation. This simulation is used to perform calculation of hydrocarbon resources through probabilistic analysis on Main Interval. Based on identification result of closure on depth structure map of top Main Interval, there are seven closure that will be evaluated as prospect area in this research. Evaluation of these prospects is to perform calculations of petroleum resources and petroleum system analysis at Osram Area. The final result of this research is a sequence of prospect ranking based on each prospect evaluation. Based on calculation result of Montecarlo Simulation, the petroleum unrisk resources of Main Interval in Osram Area is 12,44 MMSTB. The ranking of these prospects form the highest to the lowest are: Prospect-7, Prospect-4, Prospect-2, Prospect-3, Prospect-1, Prospect-5, and Prospect-6.